2008
DOI: 10.1111/j.1567-1364.2008.00397.x
|View full text |Cite
|
Sign up to set email alerts
|

Btn2p is involved in ethanol tolerance and biofilm formation in flor yeast

Abstract: Flor yeasts are a particular kind of Saccharomyces cerevisiae strains involved in Sherry wine biological ageing. During this process, yeasts form a film on the wine surface and use ethanol as a carbon source, producing acetaldehyde as a by-product. Acetaldehyde induces BTN2 transcription in laboratory strains. Btn2p is involved in the control of the subcellular localization of different proteins. The BTN2 gene shows a complex expression pattern in wine yeast, increasing its expression by acetaldehyde, but repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…In the present study, we focused on BTN2 whose deficiency induces hypersensitivity to ethanol (Espinazo-Romeu et al, 2008; Yang et al, 2011). BTN2 encodes a v-SNARE binding protein that is involved in intracellular protein trafficking (Kama et al, 2007) and plays a role in protein deposition in the nucleus (Miller et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we focused on BTN2 whose deficiency induces hypersensitivity to ethanol (Espinazo-Romeu et al, 2008; Yang et al, 2011). BTN2 encodes a v-SNARE binding protein that is involved in intracellular protein trafficking (Kama et al, 2007) and plays a role in protein deposition in the nucleus (Miller et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…BTN2 encodes a v-SNARE binding protein that is involved in intracellular protein trafficking (Kama et al, 2007) and plays a role in protein deposition in the nucleus (Miller et al, 2015). Because Btn2 is important for the correct localization of various proteins, btn2 Δ cells show pleiotropic phenotypes, including decreased resistance to ethanol, acidic pH, hydrostatic pressure, and L -canavanine (Chattopadhyay et al, 2000; Chattopadhyay and Pearce, 2002; Kim et al, 2005; Espinazo-Romeu et al, 2008; Yang et al, 2011). We found that BTN2 mRNA was efficiently translated under severe ethanol stress and that Btn2 protein levels decreased after ethanol elimination.…”
Section: Introductionmentioning
confidence: 99%
“…Its deletion affects the biofilm formation ability of flor yeasts, and it increases its sliding motility, resulting in increased mat formation. This correlates with an increased transcription of the FLO11 gene, essential for biofilm formation [10]. Similar studies have concentrated on overexpressing genes SOD1, SOD2, and HSP12 in different veil-forming yeast strains showing that the veil formation by these strains took place more rapidly, and the veil was thicker and with higher percentages of viable cells.…”
Section: The Outlook For the Future Of The Veil-forming Yeastsmentioning
confidence: 95%
“…The veil of flor in Sherry wines consists of multicellular aggregates composed, in turn, by yeasts, bacteria, and fungi, with yeasts being the main microorganisms [4,6,[8][9][10][11][12]. Within the different species of yeasts, Saccharomyces cerevisiae is the most popular species found in the different wines elaborated under biological ageing.…”
mentioning
confidence: 99%
“…Six hundred yeast strains were isolated previously from the veil of flor of "Manzanilla" and "Fino" wines, from the Sanlúcar de Barrameda and Jerez wineries (Cádiz, Spain), respectively [2,17]. After a first screening, using a Mitochondrial DNA restriction analysis and electrophoretic karyotyping by pulsed-field-gel electrophoresis (PFGE) and SSR-Multiplex PCR, eighteen different profiles of Saccharomyces strains were shown and then grouped according to their similarities-eight from "Manzanilla", denoted as MI to MVI, MX and MXVIII, and ten from "Fino", coded as FI to FX, respectively.…”
Section: Yeast Strainsmentioning
confidence: 99%